EFFECT OF CURING BY DIFFERENT POLLUTED WATER ON THE STRUCTURAL BEHAVIOR OF RC SLABS - Majeed, Muhannd Waleed; Mohammed Abd, Lubna; Abbas, Aamer Najim (Journal of Applied Engineering Science, 2021)
There was a serious water problem especially in the region close to the sewer treatment plants. Therefore, an effort has been made to utilize the waste water from the sewer treatment plants for building purposes, so that the water problem can be greatly minimized and the waste water can be properly disposed of for good environmental conservation. Foundation panels in severe curing conditions performed by hospital waste water and sewer waste water.. This article highlights an experimental analysis on the behavior of concrete foundations in severe curing conditions performed by hospital waste water and sewer waste water. The experiment measured ultimate load, first crack load, load-deflection behavior, stiffness and evaluated the crack pattern of 12 reinforced concrete foundation panels after curing the specimens for 28 days. The results of the test indicate that the use of hospital and sewer waste water could reduce the strength, stiffness and accelerate damage of tested panels. Mechanical properties such as compressive strength, elastic modulus, flexural strength, etc. were examined by pouring various concrete samples in the element of cubes, cylinders and prisms, etc. and were concluded to be acceptable.